(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: Assessment of the nutritional status of chemotherapy-radiotherapy patients for hypopharynx-larynx cancer stage III-IV at the National Otorhinorarynology hospital of Vietnam in 2022. Subjects and study methods: Cross-sectional descriptive assessment of nutritional status at hospital stays on days 1st, 15th, and 30th of 50 patients suffering from pharynx-larynx cancer stage iiiiv. Results: The mean age of the patients was 54.3 years old, and most of them were men. On the 1st day 44.0% patients were malnourished by BMI classification and 86.0% of patients were underweight or at risk of malnutrition by PG-SGA (B or C). After 30 days of follow-up, the rates increased to 56.0% (BMI) and 98.0% (PG-SGA), in which 52.0% of patients have weight loss (26/50 patients). Conclusion: The malnutrition rate in patients suffering from hypopharynx-larynx cancer stage III-IV with chemotherapy-radiotherapy at the National Otorhinorarynology hospital of Vietnam in 2022, according to BMI, was relatively high and increased with the duration of hospital stay. Evaluation according to PG-SGA showed that the majority of patients were severely malnourished.